BIOLOGIC AND PHOTOCATALYTIC DEGRADATION OF UV PRETREATED MIXTURE OF DYES BY CALOCYBE INDICA - VENKATA KRISHNA BAYINENI; S. MAHESWARI; MALAIYARASA PANDIAN P (Innovare Journal of Sciences, 2024)
The degradation of a mixture of dyes by photocatalytic process (TiO₂/UV) and as a pre-treatment to biologic degradation by Calocybe indica (milky white mushroom) was investigated. The fungus was capable of degrading 52.6% of the dye’s mixture, within 10 days under static conditions at pH 7.5 and 30°C temperature and having 150 μg/ml dye concentration. The photocatalytic process was capable of degrading only 16.2% dye mixture when exposed to UV for 4 h at continuous stirring at 30°C temperature and 150 μg/mL dye concentration. A two-step treatment process, namely, photocatalytic treatment followed by biologic degradation, was assessed. The visual observations and ultraviolet-visible (UV-VIS) spectral analysis showed that the combined effects were most efficient in the removal of the dye (94.6%), which involved a complex interaction of enzyme activity, biosorption, and photocatalytic action. The biotransformation of the synthetic dye mixture was confirmed by UV-Vis spectroscopy analyses of samples before and after decolorization. The strain showed a high correlation between the dry weight and color removal percentage. Thus, the biodegradation of complex synthetic dye mixture to non-toxic metabolites using C. indica would be a better option for the biologic treatment of textile effluents.